Aflatoxin proficiency testing and control in Kenya - Herrman, Timothy J.; Hoffmann, Vivian; Muiruri, Anne; McCormick, Cindy (International Association for Food Protection, 2020)
Texas A&M AgriLife Research (hereafter AgriLife) introduced a quality systems approach to accurately measure and manage aflatoxin that resulted in improved food safety for approximately 10 million Kenyans. A quality systems approach contains elements that ensure laboratory testing competence. In this study, quality system elements included analyst training and qualification, proficiency testing, use of reference material to support analytical traceability and define analytical uncertainty, development and implementation of a food safety plan by commercial maize (Zea mays) millers, and verification of testing accuracy at the AgriLife laboratory accredited by the Kenya Accreditation Service under the International Organization for Standardization/International Electrotechnical Commission 17025:2005 standard. In 2014 and 2015, five proficiency rounds were performed, ranging in aflatoxin concentrations of 5 to 40 μg/kg. Five laboratories had a z-score of >3, and all of these were for the fifth proficiency round with an aflatoxin content of 5 μg/kg. In 2015, 31 analysts qualified to participate in the program at 15 maize mills. The analysts' qualification for seven test samples, which ranged from 3.1 to 28 μg/kg total aflatoxin, resulted in an average relative standard deviation of 19.2% across all participants and test methods. Independent testing of participating mill verification results before and after analyst implementation of the quality systems approach revealed an improvement in measure accuracy.